﻿Description of immature stages of Gymnetron species (Coleoptera, Curculionidae, Curculioninae), with particular emphasis on the diagnostic morphological characters at the generic and specific levels - Skuhrovec, Jiří; Gosik, Rafał; Caldara, Roberto; Toševski, Ivo; Batyra, Aleksandra (ZooKeys, 2022)
The immature stages of the following five Palaearctic Gymnetron species are described for the first time: G.tibiellum Desbrochers des Loges, 1900, G.veronicae (Germar, 1821), G.rotundicolle Gyllenhal, 1838, G.melanarium (Germar, 1821), and G.villosulum Gyllenhal, 1838. These species belong to four different groups previously established according to a phylogenetic analysis: the first two belong to the G.veronicae group and the other three to groups respectively bearing their name (G.rotundicolle, G.melanarium, and G.villosulum groups). All these species exhibit several diagnostic characters distinguishing them from each other. Some characters that can be used to separate Gymnetron from other genera in the tribe are also suggested. Three highly significant characters for the larvae and three for the pupae were identified. For the larvae they are: (1) labial palpi with single palpomeres, (2) all spiracles unicameral, and (3) epipharynx with a single pair of mes or none at all. For the pupae they are: (1) the pronotum with prominent pronotal protuberances, (2) abdominal segment VIII with a conical abdominal protuberance dorsally, and (3) very short or even reduced urogomphi. The species studied here are compared with those Gymnetron species already known and with other genera in the tribe Mecinini. Keys to the larvae and pupae described here are provided. All the characters used for identification are illustrated by photographs or drawings.
Keywords: weevils; morphology; Mecinini; taxonomy; mature larva; pupa; Biology